Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien Pengguna BPJS Kesehatan di RSU Muhammadiyah Mandala by Pass Medan - Risna Dewi; Muhammad Hilman Fikri; Arief Hadian; Muhammad Rahmat (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The purpose of this study was to determine the effect of service quality on patient satisfaction using BPJS Kesehatan at the Rumah Sakit Umum Muhammadiyah Mandala By Pass Medan. The population in this study were patients using BPJS Kesehatan at the RSU Muhammadiyah Mandala By Pass Medan. which amounted to 706 people. The sample in this study amounted to 256 people taken randomly using random sampling technique. This type of research is quantitative research. The data collection instrument used a questionnaire and direct observation of spaciousness which was then analyzed using the multiple linear regression analysis method Y = 8.170 + 0.515 + e, which means that the quality of service affects patient satisfaction. Furthermore, testing with the t test showed 16,376 > 1.65, so it can be concluded that the service quality variable has a significant effect on patient satisfaction. R square shows the coefficient of determination is 0.514, meaning that service quality affects patient satisfaction by 51.4%, while the remaining 48.6 is influenced by other variables not examined in this study.